2019
DOI: 10.1186/s12906-019-2767-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of a methanol extract of Dictamnus dasycarpus Turcz. root bark on imiquimod-induced psoriasis

Abstract: BackgroundThe root bark of Dictamnus dasycarpus Turcz. has been successfully used for the treatment of inflammatory skin conditions such as eczema and pruritus. However, the anti-psoriatic effect of this plant has not until now been investigated.MethodsThe aim of this project was to investigate whether a methanol extract of Dictamnus dasycarpus Turcz. root bark (MEDD) can be used as a therapeutic agent for psoriasis in C57BL/6 mice model of imiquimod (IMQ)-induced psoriasis. IMQ and MEDD was applied to mouse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In addition, it has been reported that Lonicera japonica inhibits the NF-κB and signal transducer and activator of transcription 3 pathway (STAT3) in acute inflammation through a component called chrysoeriol [23]. Furthermore, Choi et al (2019) have demonstrated that Dictamnus dasycarpus Turcz has an anti-inflammatory effect through lowering inflammatory cytokines such as interferon-γ and interleukin (IL)-17 [10]. As another example, avarol, a marine sesquiterpenoid hydroquinone derived from Dysidea avara (Dysideidae family), displays beneficial properties such as anti-inflammatory and antioxidant effects and it has been suggested as a material possessing potential UVB photoprotective candidates [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that Lonicera japonica inhibits the NF-κB and signal transducer and activator of transcription 3 pathway (STAT3) in acute inflammation through a component called chrysoeriol [23]. Furthermore, Choi et al (2019) have demonstrated that Dictamnus dasycarpus Turcz has an anti-inflammatory effect through lowering inflammatory cytokines such as interferon-γ and interleukin (IL)-17 [10]. As another example, avarol, a marine sesquiterpenoid hydroquinone derived from Dysidea avara (Dysideidae family), displays beneficial properties such as anti-inflammatory and antioxidant effects and it has been suggested as a material possessing potential UVB photoprotective candidates [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, many plants have been proven to show anti-inflammatory effects on the skin as follows: Angelica gigas [ 8 ], Lonicera japonica [ 9 ], Dictamnus dasycarpus Turcz. [ 10 ], D. opposita Thunb. [ 11 ], Ulmus davidiana var.…”
Section: Introductionmentioning
confidence: 99%
“…The extract treated lesions exhibited infiltration of the immune cells in the dermis, reduction in scaly skin and epidermal hyperplasia. The extract reduced interleukin IL-17 and interferon IFN-γ levels, the number of Th17 cells and γδT cells, and the size of the Th1 cells and STAT3 signals 94 .…”
Section: Magnolia Officinalis Contains a Biphenolicmentioning
confidence: 92%
“…A methanolic extract of root bark of Dictamnus dasycarpus Turcz. improved scaly skin lesions, reduced the number of in ammatory cell in ltration, and decreased epidermal thickness in IMQ-induced psoriasis mice by inhibiting STAT3 signaling pathway and reducing the number of Th17 cells as well as IL-17 production [84]. 9,19cycloartenol glycosides G3, the main component of Cimicifuga simplex exhibited anti-psoriatic effects by suppressing the differentiation of CD4 + T cell into Th17 phenotype and inhibiting IFN-γ-induced JAK/STAT activation [85].…”
Section: Multiple Signaling Pathways Jak/stat and Related Signaling Pathwaysmentioning
confidence: 97%